A COMPARATIVE STUDY ON ISRAELI PRIME MINISTER'S REACTION TO KOMPAS GRAMEDIA GROUP AND MEDIA NUSANTARA CITRA IN THE JANUARY 2024 EDITIONS REGARDING SOUTH AFRICA'S LAWSUIT AGAINST ISRAEL FOR GENOCIDE IN GAZA, PALESTINE - Bahanan, Umar Fauzi (Universitas Nasional, 2024)
The invasion of the Palestinian Gaza region by Israel following the events of October 7, 2023, has garnered widespread international attention, particularly concerning the suffering of children and women. In response, a group of South African lawyers filed a lawsuit against Israel in the International Court of Justice (ICJ) in The Hague, citing the Genocide Convention. This legal action led to public statements from Israeli Prime Minister Benjamin Netanyahu, which were covered extensively by major Indonesian media organizations, including Kompas Gramedia Group (KG Group) and Media Nusantara Citra (MNC Group). This study employs a qualitative descriptive analysis to examine Netanyahu's political communication in relation to the ICJ decision, focusing on his response to the South African lawsuit. News coverage from both KG Group and MNC Group in January 2024 is compared through the lens of Media Agenda Setting theory, which emphasizes the media's role in shaping public perception. Utilizing Heidegger's hermeneutical analysis method, the research identifies significant differences in how the two media outlets present the issue. KG Group emphasizes the human-interest angle, focusing on the emotional and personal dimensions of the conflict, while MNC Group adopts a more cautious stance, particularly in its reporting on the Israeli government. This comparative analysis underscores the differing editorial priorities of the two media groups and highlights their respective approaches to covering the ongoing Gaza conflict and international responses.